Perceived Ease of Use, Perceived Usefulness and Perceived Trust on Behavior Intention to Use Mobile Banking - Putri, Elma Nazila; Sabaruddin, La Ode (Amkop Management Accounting Review (AMAR), 2025)
This study was conducted to determine the influence of Perceived Ease of Use, Perceived Usefulness, and Trust on the Intention to use m-banking technology among BRI bank customers, using the Technology Acceptance Model (TAM) developed by Davis in 1989. This study employs a quantitative method, focusing on a population of mobile banking users at BRI Bank in Kendari City. The sample was obtained using a sampling technique, where a questionnaire was distributed to 100 respondents. The data analysis technique uses Smart PLS. The results of the study show that Perceived Ease of Use, Perceived Usefulness, and Trust significantly influence the Behavior Intention to Use Mobile Banking, with a path coefficient that has a substantial impact on interest in using Mobile Banking at Bank BRI in Kendari City.